Assessment of consistency of minimum post-mortem intervals estimated by thermal summation-based methods in medico-legal cases associated with blowflies. (March 2023) - Palavesam, Azhahianambi; Selvakumar, R.; Latha, Bhaskaran Ravi; Jyothimol, G.; Venkataramanan, R.; Harikrishnan, T.J.
Highlights: Consistency of PMI estimated using six thermal summation constants was good to excellent. The variation in the mean difference of PMI was higher in thermal summation methods based on C. rufifacies. This study reconfirmed that the PMI is a range of value and not a single number. Chrysomya megacephala and C. rufifacies based thermal summation constants explained 93% to 99% variance in the estimation of PMI. Described field reliable thermal summation constants of C. megacephala and C. rufifacies for PMI estimation with lowest margin of error. Abstract: Background: This study is based on blow fly samples collected from 8 medico-legal cases in Tamil Nadu, India. The fly life stages were identified and the consistency of minimum post-mortem intervals (PMImin) estimated by different thermal summation-based methods was assessed. Methods: PMImin of 8 medico-legal cases was estimated using six different thermal summation constants and lower developmental temperatures that are based on C. megacephala and C. rufifacies developmental data. Limits of agreement (LoA), intra class correlation coefficient (ICC) between PMImin values and margin of error of mean of difference between PMImin values were calculated. Results: Intra-class correlation between the PMImin values estimated using different thermal summation constants based on C. megacephala ranged between 0.89 and 0.98 and coefficient of determination ranged between 0.93 and 0.98. Intra-class correlation between the PMImin values estimated using different thermal summation constants based on C. rufifacies ranged between 0.91 and 0.99 and coefficient of determination ranged between 0.95 and 0.99. The mean difference of PMImin values estimated using different thermal summation methods based on C. megacephala ranged between 1.8 hr and 6.6hr and margin of error ranged between 2.51 and 6.93hr. The mean difference of PMImin values estimated using different thermal summation methods based on C. rufifacies ranged between 3.33 and 31.33hr and margin of error ranged between 4.66 and 32hr. Conclusion: Consistency of PMImin values estimated by different thermal summation methods was good to excellent. Thermal summation constants useful in estimation of PMImin with lowest mean difference and margin of error were described.